Would You Kindly Consider the Consequences? - Yvette Ann Walker (Press Start, 2015)
This article seeks to introduce the application of laws to the plot lines of videogames as a source of legal scholarship and reflexive social critique through an analysis of the legal liability for the killing of Big Daddies in Bioshock.